Lability and solubility of trace metals in soils - Mao, Lingchen (2014)
The continuing need for improved assessment of risk from heavy metal contamination of the environment has prompted scientific interest in quantifying and predicting metal solubility, ‘lability’ and bioavailability. This has led to the development of new techniques to fractionate and speciate trace metals in soils. The objectives of the current study were to increase understanding of the effects of (i) soil properties, (ii) contaminant source and (iii) contact time on metal lability and solubility in soils. Multi-stable isotope dilution (ID) methods were used to determine the lability (E-values) of Ni, Cu, Zn, Cd and Pb in soils, alongside more traditional approaches employed for metal fractionation including single and sequential extraction procedures. Most of the work was undertaken using (i) archived soils amended by metal salts (MA soils; n=23) and (ii) topsoils collected from Nottingham, Wolverhampton and London (Urban soils; n=100). The resulting data was used first to quantify the factors affecting trace metal lability in the MA soils using a logistic (S-shape) model which described metal E-value primarily as a function of soil pH with secondary influences from other soil properties. It was apparent that mineral oxides were important fixation phases for Ni, Zn and Cd while Pb was strongly affected by organic matter in soils. This model, parameterised on soils contaminated originally by metal nitrate solution, was then applied to the Urban soils to reveal the extent to which contaminant source still controlled metal lability. A further investigation of the long-term effect of metal source on metal lability was pursued through a third dataset of rural roadside soils (n=42) which had received Pb mainly from petrol-derived and geogenic sources, defined by their isotopic signature. It was demonstrated that petrol-derived Pb remained more labile than Pb from the parent material, despite decades of contact, although both petrol-derived and geogenic Pb contributed to both the labile and non-labile fractions. In a fourth dataset, soils that had received Pb from sewage sludge amendment (n=16), the co-existence of high phosphate concentration from sewage sludge limited the magnitude and range of Pb lability, probably through formation of Pb-phosphate minerals. No consistent agreement was found between labile fraction of Pb and any single sequential extraction (SEP) fraction in all soils contaminated by Pb from multiple sources.